Past Meets Present Archaeologists Partnering with Museum Curators, Teachers, and Community Groups - Jameson, John H.; Baugher, Sherene (Springer New York : Imprint: Springer, 2007)
In these times of decreasing funding to humanities and social sciences, program directors are reluctant to undertake outreach projects that they assume require large budgets. The selected case studies in Past Meets Present, however, reflect modest start-up costs, demonstrating that success need not be tied to big bank rolls. The lesson to be derived from these modestly funded projects is that peoples' attitudes and initiatives make the difference. Focusing on a broad range of successful public archaeological programs in schools and local communities, this book addresses a wide range of developments and standards for effective public interpretation, education, and outreach in archaeology. Past Meets Present provides the reader with models for implementing public outreach programs with an emphasis on collaborative partnerships. Only when archaeologists are willing to reach out to people in other professions and work with and learn from the community can successful partnerships be formed. Past Meets Present describes effective models of collaboration that enable the archaeology of the past to meet the educational and interpretive needs of the present. Cover photo courtesy of John H. Jameson, Jr. and the painting "Unlocking the Past" by Martin Pate is courtesy of the Southeast Archaeological Center, National Park Service.